2020
DOI: 10.24127/pj.v9i2.3075
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extracurricular Activity Toward English Learning Achievement of Nursing Students

Abstract: This research is a descriptive correlative study. The purpose of this study was to determine the effect and relationship of English extracurricular activities (English Club) on the English learning achievement of nursing students. This research took place at the Academy of Nursing Kesdam Iskandar Muda Banda Aceh. The population in this study were all students of the Academy of Nursing Kesdam Iskandar Muda Banda Aceh. The samples are students of 2018/2019 who take part in English extracurricular activities as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This supports the idea held forth by Fredricks and Eccles (2006) asserting that students who take part in extracurricular activities depict a higher level of communicative competence and distinctly better learning outcomes. This goes in line with the research result conducted to nursing students in Indonesia by Juliana and Afrianti (2020) claiming that extracurricular activities can influence the learning outcomes of English. Also, in a school in Indonesia, Neno and Siahaan (2021) conducted a study by comparing students who participated in English club programs and those who did not, using a pre-test and a post-test as research tools.…”
Section: Extracurricular Activities To Enhance English Learning In Ef...supporting
confidence: 86%
“…This supports the idea held forth by Fredricks and Eccles (2006) asserting that students who take part in extracurricular activities depict a higher level of communicative competence and distinctly better learning outcomes. This goes in line with the research result conducted to nursing students in Indonesia by Juliana and Afrianti (2020) claiming that extracurricular activities can influence the learning outcomes of English. Also, in a school in Indonesia, Neno and Siahaan (2021) conducted a study by comparing students who participated in English club programs and those who did not, using a pre-test and a post-test as research tools.…”
Section: Extracurricular Activities To Enhance English Learning In Ef...supporting
confidence: 86%
“…After being consulted with the rtable, r11 = 1,000> rtable = 0.950 with N = 5. That is, with a trial of 5 students, the r11 is greater than the rtable, so the questionnaire is declared reliable and can be used as a research instrument (Juliana & Afrianti, 2020;Purnamasari, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies argue that the formation of an English Club extracurricular activity can add insight and good experience for students and teachers involved in these activities [5], [6]. Another study also revealed that students could also improve their language achievement by joining the English Extracurricular [7].Thus, to improve the English language skills of students at SMP Garuda, Tangerang. A community service program was held in assisting the formation of the English Club Extracurricular at SMP Garuda, Tangerang.…”
Section: Introductionmentioning
confidence: 99%